Helicobacter pylori-negative Russell body gastritis: does the diagnosis call for screening for plasmacytic malignancies, especially multiple myeloma? - Klair, Jagpal Singh (BMJ Publishing Group, 2014)
Russell body gastritis (RBG) is a rare entity with unestablished pathophysiology, endoscopic findings, clinical manifestations and treatments. Literature is scarce on this clinical entity with unclear clinical significance. Of 18 cases reported, 12 tested (+) for Helicobacter pylori and improved with treatment, but it remains unclear whether this link is coincidental or bears some clinical significance. We describe a case of elderly woman who had a follow-up oesophagogastroduodenoscopy for chronic peptic ulcers, and biopsy showed positive immunohistochemical stains for κ and λ, indicating a polytypic population of plasma cells. Immunostaining for H pylori was negative. Biopsies were also (−) for gastric carcinoma, lymphoma and plasmacytoma. Considering her RGB-suggestive histology and her symptoms of bone pains and anaemia, multiple myeloma screening was considered clinically relevant. The purpose of this review was to educate clinicians and gastroenterologists about this unique entity and explore its association with multiple myeloma or other plamacytic malignancies.